On the Security of Rate-limited Privacy Pass - Chu, Thi Thu Hien; Do, Khue; Hanzlik, Lucjan (CCS '23: Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security, 2023)
The privacy pass protocol allows users to redeem anonymously issued cryptographic tokens instead of solving annoying CAPTCHAs. The issuing authority verifies the credibility of the user, who can later use the pass while browsing the web using an anonymous or virtual private network. Hendrickson et al. proposed an IETF draft (privacypass-rate-limit-tokens-00) for a rate-limiting version of the privacy pass protocol, also called rate-limited Privacy Pass (RlP). Introducing a new actor called a mediator makes both versions inherently different. The mediator applies access policies to rate-limit users' access to the service while, at the same time, should be oblivious to the website/origin the user is trying to access. In this paper, we formally define the rate-limited Privacy Pass protocol and propose a game-based security model to capture the informal security notions introduced by Hendrickson et al.. We show a construction from simple building blocks that fulfills our security definitions and even allows for a post-quantum secure instantiation. Interestingly, the instantiation proposed in the IETF draft is a specific case of our construction. Thus, we can reuse the security arguments for the generic construction and show that the version used in practice is secure.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Cryptography; Security and Privacy